2017
DOI: 10.1590/0100-3984.2015.0224
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging of suspicious (BI-RADS 4) breast lesions: stratification based on histopathology

Abstract: Objective:To test the use of diffusion-weighted imaging (DWI) in stratifying suspicious breast lesions (BI-RADS 4), correlating them with histopathology. We also investigated the performance of DWI related to the main enhancement patterns (mass and non-mass) and tested its reproducibility.Materials and Methods:Seventy-six patients presented 92 lesions during the sampling period. Two independent examiners reviewed magnetic resonance imaging studies, described the lesions, and determined the apparent diffusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Diffusion-weighted imaging is able to differentiate between malignant and nonmalignant lesions, exhibiting a better performance for mass evaluation. 34 Furthermore, reports have indicated that ADC obtained from DWI is capable of acting as a biomarker in the evaluation of early responses to treatment in various forms of cancer. 35 Consistent with clinical literature, during our study, a significant change in tumor ADC values was observed following chemoradiotherapy treatment, which we considered as being positive response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging is able to differentiate between malignant and nonmalignant lesions, exhibiting a better performance for mass evaluation. 34 Furthermore, reports have indicated that ADC obtained from DWI is capable of acting as a biomarker in the evaluation of early responses to treatment in various forms of cancer. 35 Consistent with clinical literature, during our study, a significant change in tumor ADC values was observed following chemoradiotherapy treatment, which we considered as being positive response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI), magnetic resonance spectroscopy (MRS), and other quantitative imaging techniques in diagnosing breast BI-RADS 3-5 lesions have been explored extensively to aid in diagnosis specificity. Relaxation time could be another quantitative MR method for the diagnosis of breast diseases (9)(10)(11)(12)(13)(14)(15). Previous studies have shown that quantitative longitudinal relaxation time (T1) and transverse relaxation time (T2) values could assess the histopathology of breast diseases and, thus, be used as a potential biomarker of biopsy (16,17).…”
Section: Introductionmentioning
confidence: 99%